1192 The Accuracy of a Novel Sleep Ring Device for Estimating Sleep Onset with Good and Poor Sleepers. (27th May 2020) - Scott, H; Whitelaw, A; Canty, A; Lovato, N; Lack, L
Abstract: Introduction: THIM is a new ring-like sleep device that, if found to accurately measure sleep onset, could be used for a variety of clinical purposes. These include administering a brief but effective treatment for insomnia called Intensive Sleep Retraining, facilitating the optimal 10-minute power nap, and administering Multiple Sleep Latency Tests (MSLTs) outside of the sleep laboratory. This study assessed the accuracy of THIM for measuring sleep onset latency compared to polysomnography (PSG). Methods: Twenty healthy individuals aged 23.6 years ( SD = 4.89) underwent overnight PSG recording whilst using THIM on two nights in the sleep laboratory, one week apart. On each night, participants completed sleep onset trials for four hours whilst monitored via PSG. In these trials, participants attempted to fall asleep whilst responding to vibrations emitted from THIM. Once they failed to respond to two consecutive stimuli, THIM woke them with an intense vibration. Participants had a short break before attempting the next trial. Results: On average, THIM overestimated sleep onset on the first night by 0.24 minutes ( SD = 0.90). On the second night, THIM overestimated sleep onset by 0.82 minutes ( SD = 1.31) and this discrepancy was not significantly different to that obtained on the first night, p = .08. The accuracy of THIM did not differ between good sleepers (Insomnia Severity Index (ISI) score < 7) or poor sleepers (ISI score 8-15), p = .98. Conclusion: The findings suggest that THIM is accurate at estimating sleep onset latency for both good and poor sleepers. The next step is to test THIM outside of the laboratory environment. The goal is to develop an accurate yet practical device that can translate laboratory-based procedures to the home environment, to the benefit of patients and clinicians wanting to improve sleep. Support: The project was funded in-part by the manufacturers of THIM, Re-Time Pty. Ltd., with additional funding provided by Flinders University.